24 Reducing vibrations to improve infant patient safety during transportation. (29th October 2021) - Renesme, Laurent; Darwaish, Fadwa; Greenwood, Kim; Aubertin, Cheryl; Green, James; Chan, Adrian; Langlois, Robert; Redpath, Stephanie
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Each year, thousands of newborns are transported by air or ground ambulance to receive specialized medical care. For neurologically immature and physiologically compromised infants, especially preterm infants, the noise and vibration exposure during transport are high despite preventative measures, and may be an important contributor to brain injury risk. Objectives: To develop a new tool to investigate vibrations during neonatal transport and mitigation strategies. Design/Methods: Proof of concept study including 3 steps: 1) Characterization of the vibrations during transport. Accelerometer sensors placed on different layers of the Neonatal Patient Transport System (NPTS) (neonate manikin, mattress, incubator, deck, stretcher, and vehicle floor) with a variety of ambulance on road tests performed to capture data. 2) Experimentation - A shaker table was used to develop a standardized test environment. Vibration testing was performed, with the entire NPTS mounted on the shaker table. 3) Mitigation - Shaker table tests were repeated using different configurations of mattress and harness types on manikins with different bodyweights. Results: 1) Characterization: Road transport exposed the manikin's head to vibrations that exceeded adult standards. Examining the frequency spectra of the accelerometer signals across different layers of the NPTS suggests that two interfaces, stretcher/vehicle floor and incubator/deck, may be critical for intervention to mitigate the vibrations, as they both showed the highest gains in vibration power. 2) Experimentation: Comparison between the on-road and shaker table tests showed that the shaker table was able to reproduce on-road transportation with acceptable fidelity. The shaker table setup can serve as a standardized environment to explore the impact of several NPTS design variables on vibrations transmitted to the patient. 3) Mitigations: Different mattresses were shown to influence the vibrations experienced by the manikin. The head restraint harness type showed an amplitude reduction of the peak frequency component for all experiment types and for most mattress types compared to a standard 5-point harness. Conclusion: Our study demonstrated that: i) vibrations during neonatal transport can exceed adult standards; ii) acceptable fidelity simulation of road conditions can be achieved using a shaker table system; and iii) the most effective approach for vibration mitigation should consider the whole NTPS, instead of focusing solely on the isolette.